Negotiating complex contracts: research and development (R&D) funding and advance vaccine purchases for COVID-19 between 2020 and 2021 - King Mantilla, Katiuska (2025)
This article examines research and development (R&D) funding, the advance purchase of COVID-19 vaccines and the complex contracts that states signed with pharmaceutical companies. Drawing on information from the Centre for Global Health and the European Court of Auditors, the findings suggest that pharmaceutical companies obtained public funds for vaccine development and took advantage of their privileged position to impose contractual clauses on countries, including production/distribution conditions and compensation for vaccine side effects. The findings suggest that the big winners during the pandemic were the pharmaceutical companies, that states did not benefit from the investment made in R&D, and that some Latin American countries accepted contractual impositions, including maintaining the confidentiality and non-disclosure of contracts.